2022
DOI: 10.1002/cam4.5421
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of AML‐MRC reveals TP53 mutation as an adverse prognostic factor irrespective of MRC‐defining criteria, TP53 allelic state, or TP53 variant allele frequency

Abstract: Background Acute myeloid leukemia with myelodysplasia‐related changes (AML‐MRC) generally confers poor prognosis, however, patient outcomes are heterogeneous. The impact of TP53 allelic state and variant allele frequency (VAF) in AML‐MRC remains poorly defined. Methods We retrospectively evaluated 266 AML‐MRC patients who had NGS testing at our institution from 2014 to 2020 and analyzed their clinical outcomes based on clinicopathological feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Previously, we had shown that TP53 mutations were associated with inferior outcomes in patients with AML with myelodysplasia-related changes (AML-MRC) regardless of TP53 allelic state. 15 We sought to evaluate whether this holds true in the AML-MR cohort. A workflow to allocate TP53 allelic state in our cohort is presented in supplemental Figure 4 A.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we had shown that TP53 mutations were associated with inferior outcomes in patients with AML with myelodysplasia-related changes (AML-MRC) regardless of TP53 allelic state. 15 We sought to evaluate whether this holds true in the AML-MR cohort. A workflow to allocate TP53 allelic state in our cohort is presented in supplemental Figure 4 A.…”
Section: Resultsmentioning
confidence: 99%
“…TP53 mutations are frequently associated with complex karyotype, negative correlation with other gene mutations, and dismal outcomes regardless of therapy. 2 , 4 , 15 , 21 , 22 , 23 , 24 The divergences in 2 classifications regarding TP53 are (1) WHO-HAEM5 does not have a TP53 -AML category and (2) ICC includes pure erythroid leukemia in the AML- TP53 but WHO-HAEM5 includes it in the AML-DIFF. Our results show that TP53 mutations are associated with distinct pathological features and extremely dismal outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, in the context of AML-MRC, the AML-MRC-C subtype is particularly enriched in TP53 mutations (40–55%), while the AML-MRC-H and AML-MRC-M subtypes more rarely display TP53 mutations. 102 , 103 It is of interest to note that AML-MRC-C subgroup is heterogeneous in that it can be subdivided into TP53 -mutant and TP53 -WT cases: the TP53 -mutant cases have a lower rate of mutations of RNA splicing genes and of ASXL1, BCOR and EZH2 genes compared to those TP53 -WT. 102 , 103 TP53 -mutant AML-MRC-C are associated with cytogenetic abnormalities in 5q, 7q, 17p and complex karyotype and are associated with poor outcome, independently of their multi-hit or single-hit TP53 mutational status.…”
Section: Tp53-mutated Mds and Amlmentioning
confidence: 99%